Road Capacity, Domestic Trade and Regional Outcomes - A. Kerem Cosar; Banu Demir Pakel; Devaki Ghose; Nathaniel Young (Center for Economic Studies and ifo Institute (CESifo), 2021)
What is the impact on intra-national trade and regional economic outcomes when the quality and lane-capacity of an existing paved road network is expanded significantly? We investigate this question for the case of Turkey, which undertook a large-scale public investment in roads during the 2000s. Using spatially disaggregated data on road upgrades and domestic transactions, we estimate a large positive impact of reduced travel times on trade as well as local manufacturing employment and wages. A quantitative exercise using a workhorse model of spatial equilibrium implies heterogeneous effects across locations, with aggregate real income gains reaching 2-3 percent in the long-run. Reductions in travel times increased local employment-to-population ratio but had no effect on local population. We extend the model by endogenizing the labor supply decision to capture this finding. The model-implied elasticity of employment rates to travel time reductions captures about one-third of the empirical elasticity.
Keywords: F14; R11; R41; 330; trade; market access; transportation infrastructure